Profitabilitas, Koefisien Respon Laba, dan Kesempatan Bertumbuh sebagai Variabel Pemoderasi - Putra, Putu Ariyuda; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 33 No 11 (2023), 2023)
This research aims to determine the effect of profitability on the earnings response coefficient, as well as the moderating effect of growth opportunities on the relationship between profitability and the earnings response coefficient. This research examines 216 financial reports published by mining companies listed on the Indonesia Stock Exchange in 2017-2021. Profitability is proxied by ROA and ROE operated as independent variables; growth opportunities proxied by the MBV and Ln (RE) ratio are operated as moderating variables; and control variables in this research include company size, company age, and capital structure. Signal theory is used to explain research findings. To achieve the research objectives, this research uses multiple linear regression analysis. The analysis results show that profitability has a significant effect on the earnings response coefficient, and growth opportunities can moderate the effect of profitability on the earnings response coefficient. The implications of this research provide additional information regarding the earnings response coefficient which is significantly influenced by the company's ability to generate profits, the moderating effect of retained earnings weakens this influence. Keywords: Earnings response coefficient; mining companies; profitability; growth opportunity; signaling theory